Identification of main issues affecting the growth of graduates’ small and medium enterprises (SMES) in Yogyakarta - Hety Budiyanti; Shine Pintor S Patiro (Jurnal Siasat Bisnis, 2015)
After the economic crises hit Indonesia in 1997 and 2008 and contributed to downfall of a large number of big businesses in various industries. However, the small and medium enterprises (SMEs) sector has managed to survive from the crisis by showing a significant growth and rising contribution to the economy of Indonesia. Yogyakarta which is known as a city of student has acknowledged the important role of SMEs sector to improve the economic activity of the region and push the income of the people. Rising paradigm at universities and colleges in Yogyakarta about creating entrepreneurship from their graduates has contributed to the rise of graduates’ business in this place. The aim of the paper is to take a fresh look into graduate’ entrepreneurship on SMEs’ scale and competences in Yogyakarta. This paper focuses on a detailed study into the entrepreneurial activities of graduates in Yogyakarta and principally examines issues affecting their business development. Seven main issues were investigated: business establishment; location; premises (size, cost, tenure); concerns; advice utilization; education and training; and support requirements. The sample of the study was assembled from the ministry of department industry and KADIN Yogyakarta branch as formal sources. Other sample sources considered are entrepreneurship associations such as Konsultan Pengembangan Ide dan Usaha ARN of Yogyakarta. Data collecting methods used in this paper are in depth interviews and structured and semi structured questionnaires. Research method will relied mostly on ethnographic techniques.